THE ANALYSIS ON THE DISC JOCKEY TRAINING MODEL AT LA STUDIO DJ SCHOOL - Sarkol, Joseph Agustinus Friets; Latuni, Glenie; Dumais, Franklin (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims to present a holistic approach in developing DJ skills for students at LA Studio DJ School. The research method applied is a qualitative method rooted in the philosophy of positivism, specifically designed to study the condition of objects scientifically. Researchers, as the key instrument, used purposive and snowball data sampling techniques, with data collection techniques through triangulation. Data analysis was carried out inductively and qualitatively, with an emphasis on meaning rather than generalization. Additionally, LA Studio DJ School also incorporates business elements of the music industry into the curriculum, providing students with an understanding of event management, self-marketing, and building a professional network. With a focus on practical teaching and direct guidance from experienced instructors, this program aims to train high-quality DJs who are ready to compete in the dynamic music industry. Students will develop their own unique style while understanding the essence of the art of DJing and appreciating the diverse forms of expression in the world of music.